Step
*
1
1
1
of Lemma
strong-continuity-implies4
1. F : (ℕ ⟶ ℕ) ⟶ ℕ
2. M : n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ (ℕn?)
3. ∀f:ℕ ⟶ ℕ. (↓∃n:ℕ. (((M n f) = (inl (F f)) ∈ (ℕ?)) ∧ (∀m:ℕ. ((↑isl(M m f)) 
⇒ ((M m f) = (inl (F f)) ∈ (ℕ?))))))
4. f : ℕ ⟶ ℕ
5. n : ℕ
6. (M n f) = (inl (F f)) ∈ (ℕ?)
7. ∀m:ℕ. ((↑isl(M m f)) 
⇒ ((M m f) = (inl (F f)) ∈ (ℕ?)))
⊢ <mu(λn.isl(M n f)), Ax> ∈ ∃n:ℕ. ((M n f) = (inl (F f)) ∈ (ℕ?))
BY
{ ((Assert isl(M n f) = isl(inl (F f)) BY (EquationFromHyp (-2) THEN Auto)) THEN Reduce -1) }
1
1. F : (ℕ ⟶ ℕ) ⟶ ℕ
2. M : n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ (ℕn?)
3. ∀f:ℕ ⟶ ℕ. (↓∃n:ℕ. (((M n f) = (inl (F f)) ∈ (ℕ?)) ∧ (∀m:ℕ. ((↑isl(M m f)) 
⇒ ((M m f) = (inl (F f)) ∈ (ℕ?))))))
4. f : ℕ ⟶ ℕ
5. n : ℕ
6. (M n f) = (inl (F f)) ∈ (ℕ?)
7. ∀m:ℕ. ((↑isl(M m f)) 
⇒ ((M m f) = (inl (F f)) ∈ (ℕ?)))
8. isl(M n f) = tt
⊢ <mu(λn.isl(M n f)), Ax> ∈ ∃n:ℕ. ((M n f) = (inl (F f)) ∈ (ℕ?))
Latex:
Latex:
1.  F  :  (\mBbbN{}  {}\mrightarrow{}  \mBbbN{})  {}\mrightarrow{}  \mBbbN{}
2.  M  :  n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  \mBbbN{})  {}\mrightarrow{}  (\mBbbN{}n?)
3.  \mforall{}f:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}
          (\mdownarrow{}\mexists{}n:\mBbbN{}.  (((M  n  f)  =  (inl  (F  f)))  \mwedge{}  (\mforall{}m:\mBbbN{}.  ((\muparrow{}isl(M  m  f))  {}\mRightarrow{}  ((M  m  f)  =  (inl  (F  f)))))))
4.  f  :  \mBbbN{}  {}\mrightarrow{}  \mBbbN{}
5.  n  :  \mBbbN{}
6.  (M  n  f)  =  (inl  (F  f))
7.  \mforall{}m:\mBbbN{}.  ((\muparrow{}isl(M  m  f))  {}\mRightarrow{}  ((M  m  f)  =  (inl  (F  f))))
\mvdash{}  <mu(\mlambda{}n.isl(M  n  f)),  Ax>  \mmember{}  \mexists{}n:\mBbbN{}.  ((M  n  f)  =  (inl  (F  f)))
By
Latex:
((Assert  isl(M  n  f)  =  isl(inl  (F  f))  BY  (EquationFromHyp  (-2)  THEN  Auto))  THEN  Reduce  -1)
Home
Index